2016
DOI: 10.2754/avb201685010041
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between insulin-like growth factor 1 receptor gene polymorphisms in Montbeliarde cows and the birth weight of their calves

Abstract: Montbeliarde is a cattle breed of combined milk and meat performance type, which unlike the other breeds is characterized by several positive features, such as better health, high resistance to mastitis, calving ease and good weight gain. The study involved a population of 163 Montbeliarde cows. In view of the substantial role of the IGF-I/IGF-IR system in growth and development, the aim of this study was to show an association between insulin-like growth factor 1 receptor gene polymorphisms in Montbeliarde co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is worth noting that various expression levels of IGF1 may result from DNA mutations and differences in single nucleotide polymorphisms (SNPs) prevalence between the examined breeds. Previous studies have shown the effect of the SNP of the IGF-1 gene on the growth rate and meat production traits in beef cattle such as: Limousin and Hereford [ 46 ], Angus [ 47 , 48 ], Montbeliarde [ 49 ], and Hanwoo [ 50 ]. It is possible that the higher igf-1 expression level in LIM and HER bulls compared with HF further contributes to achieving higher muscle mass growth in typical beef breeds.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that various expression levels of IGF1 may result from DNA mutations and differences in single nucleotide polymorphisms (SNPs) prevalence between the examined breeds. Previous studies have shown the effect of the SNP of the IGF-1 gene on the growth rate and meat production traits in beef cattle such as: Limousin and Hereford [ 46 ], Angus [ 47 , 48 ], Montbeliarde [ 49 ], and Hanwoo [ 50 ]. It is possible that the higher igf-1 expression level in LIM and HER bulls compared with HF further contributes to achieving higher muscle mass growth in typical beef breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the IGF-1R gene have been reported in mammals (Kawashima et al, 2005;Proskura and Szewczuk, 2014;Szewczuk, 2016). When Lei et al (2008) studied the associations of the IGF-1R gene with chicken early growth and carcass traits in the Xinghua and White Recessive Rock chickens, they found that six SNPs (C17445985T, G17445596A, A17307750G, A17307494G, A17299834G, and C17293932T) were possibly associated with growth traits.…”
Section: Correlation Analysis Between Igf-1r Gene and Growth Traitsmentioning
confidence: 99%